An Analysis Of MIA Hall Psychological Conflict In Gayle Forman Novel If I Stay - Mega Maria Purba, Siti Norma Nasution (Cybernetics: Journal Educational Research and Social Studies, 2022)
This thesis Entitled An Analysis Of MIA Hall Psychological Conflict In Gayle Forman Novel If I Stay. This thesis discusses the conflict experienced by Mia as the main character in the novel If I Stay. This story tells about a young girl named Mia who faces conflict in her life. The most influential conflict in her life is psychological conflict. In this story, Mia faces two choices since her coma. She had to choose to live or die. This study focuses on the psychological conflicts experienced by Mia, and the self-defense mechanisms that Mia uses in resolving her psychological conflicts. This research uses library based and qualitative research as methods. Then, a psychological approach in the form of a defense mechanism is used to find out Mia's defense mechanism to resolve her conflict. As a result of this analysis, the most dominant conflict is psychological conflict. Psychological Mia's conflict is a conflict with herself in a coma. She was confused about whether to live or die. It makes her anxious. So, she overcomes her anxiety by some kinds of defense mechanism. They are denial, repression, reaction formation, fantasy, and displacement.